Stem cells in plastic surgery and aesthetic medicine - Czop, Julia Katarzyna; Jałowska, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
Stem cells (SCs) have multiple applications in today’s medicine including aesthetic dermatology and plastic surgery. The purpose of this paper is to review some clinical use of mesenchymal SCs. The main focus was put on adipose tissue-derived stem cells (ADSCs) as these cells are easy to harvest and because of their properties showed great potential in many studies, where they proved to accelerate wound healing, reduce scars, cause hair regrowth, or rejuvenate skin. Furthermore, when added to lipofilling procedures, such as breast augmentation they enhance fat graft survival and provide satisfying results. Currently, many different strategies for using SCs in treatments are developed with great efficacy, however, there are still many limitations and concerns regarding their clinical use.